Molecular and Clinical Markers of Pancreas Cancer - Buxbaum, James L; Eloubeidi, Mohamad A (JOP. Journal of the Pancreas, 2010)
Pancreas cancer has the worst prognosis of any solid tumor but is potentially treatable if it is diagnosed at an early stage. Thus there is critical interest in delineating clinical and molecular markers of incipient disease. The currently available biomarker, CA 19-9, has an inadequate sensitivity and specificity to achieve this objective. Diabetes mellitus, tobacco use, and chronic pancreatitis are associated with pancreas cancer. However, screening is currently only recommended in those with hereditary pancreatitis and genetic syndromes which predispose to cancer. Ongoing work to identify early markers of pancreas cancer consists of high throughput discovery methods including gene arrays and proteomics as well as hypothesis driven methods. While several promising candidates have been identified none has yet been convincingly proven to be better than CA 19-9. New methods including endoscopic ultrasound are improving detection of pancreas cancer and are being used to acquire tissue for biomarker discovery. Image: University of Southern California. Los Angeles, CA, USA (logo).